Problem Keadilan Gender dan Hak-Hak Asasi Perempuan dalam Islam - Samsuri Samsuri (Millah: Journal of Religious Studies, 2002)
This article explores the gender and human rights issues in the Islamic community, There are problems originally coming from interpretation of Islamic teachings that be gender biased. According to Riffat Hassan, a feminist of Muslim. World, it is-called as "Islamic patriarchal". In the Shariat (Islamic law) area, it id cause ddiscrimination of genderand religion. There are some factors t hatris efrom (I) cultural construction and the hegemony of interpretation authority of the sacred texts, and (2) the prejudice of cultural and the ambiguity of political interest. In this respect Abdullahi Ahmed An-Na 'im offers ideas on deconstruction of Islamic Shariat and Masdar Farid Mas 'udi about "the jiqh of empowerment" could be elaborated as a model of the awareness process for achieving of gender justice and respect of women rights in the Muslim community.